Konsep E-Tourism Dalam Pengembangan Pariwisata Era Modern - Kurniawan, Ramdhan (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
The purpose of writing this work is to understand the concept of e-tourism in the development of modern era tourism. The research method used to explore the concept of E-Tourism in modern era tourism development involves a literature review of relevant journal articles, books and recent reports. A literature search was carried out systematically using relevant keywords, such as